Development of Ludo Game Learning Media for Social Studies Subjects in Grade IV of Napallicin Elementary School - Puspita, Intan; Samitra, Dian; Sujarwo, Sujarwo (Civiliza Publishing, Indonesia., 2025)
The purpose of this study was to develop a ludo game learning media in social studies subjects in grade IV of Napallicin State Elementary School. Testing the validity. Practicality, and effectiveness of the ludo game learning media in social studies subjects in grade IV of Napallicin State Elementary School. The method used in this study is the ADDIE Development method. This development research produces a valid, practical, and effective ludo game product, namely the validity of the learning media that has been developed is included in the